Pengalihan Kewenangan Pendidikan Menengah Pada Dinas Pendidikan Provinsi Jawa Tengah (Studi Kasus : Tata Kelola Pendidik dan Tenaga Kependidikan) - Ravika Eka Setia (Journal of Politic and Government Studies, 2019)
The transfer of secondary education authority to the province based on Undang-Undang Nomor 23 Tahun 2014 concerning Regional Government has been running for two years since 2017 through the Provincial Education and Culture Office as the agency appointed to implement the policy. Implementation of a policy needs to be evaluated to see the success of a policy in achieving goals. So this study aims to determine the success of the management of educators and education personnel by the Central Java Provincial Education Office after the implementation of the policy of transferring secondary education to the province.The research method used is descriptive qualitative with data collection techniques through interviews and documentation. The data obtained are then analyzed using triangulation of methods, theories, and data sources.The results of the study revealed: 1) 1) Meeting the needs of GTK is carried out by appointing GTT and PTT to become provincial employees and the recruitment of educators and education personnel into the authority of each school to fulfill the needs of GTT and PTT; 2) PTK development activities are carried out through various activities such as the development of quality and capacity, provision of welfare, and also supervision of PTK performance; 3) Dismissal and retirement of PTK PNS according to the age limit stipulated in the law, while for GTT and PTT dismissal or termination of employment based on employment contract where for the contract period is one year that can be extended or not according to the needs of GTT and PTT by education providers.Keywords: Transfer of Authority, Manage, and Educators and Education Personnel